2007
DOI: 10.1001/archinte.167.10.1050
|View full text |Cite
|
Sign up to set email alerts
|

Intakes of Calcium and Vitamin D and Breast Cancer Risk in Women

Abstract: Background: Animal data suggest the potential anticarcinogenic effects of calcium and vitamin D on breast cancer development. However, epidemiologic data relating calcium and vitamin D levels to breast cancer have been inconclusive.Methods: We prospectively evaluated total calcium and vitamin D intake in relation to breast cancer incidence among 10 578 premenopausal and 20 909 postmenopausal women 45 years or older who were free of cancer and cardiovascular disease at baseline in the Women's Health Study. Base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
170
7
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 236 publications
(194 citation statements)
references
References 50 publications
14
170
7
3
Order By: Relevance
“…7 Similar observations of an inverse association for total vitamin D intake in premenopausal but not postmenopausal women was also recently reported by the Women's Health Study. 15 One proposed explanation lies in the interaction of vitamin D and insulin-like growth factors, thus the potential of vitamin D to suppress IGFstimulated cell growth. 34,35 Because of the decline of IGF levels with age, the effect of vitamin D on IGF-related tumor development may be more pronounced in premenopausal compared to postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7 Similar observations of an inverse association for total vitamin D intake in premenopausal but not postmenopausal women was also recently reported by the Women's Health Study. 15 One proposed explanation lies in the interaction of vitamin D and insulin-like growth factors, thus the potential of vitamin D to suppress IGFstimulated cell growth. 34,35 Because of the decline of IGF levels with age, the effect of vitamin D on IGF-related tumor development may be more pronounced in premenopausal compared to postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…Variables were entered as covariates in the logistic regression model if (i) including the covariate considerably changed the OR for the main variables of interest (>5% change in the ORs), (ii) if the covariate is a known or potential breast cancer risk factor or, (iii) if the covariate was likely to be associated with the main variable of interest (biological plausibility). OR estimates were both adjusted for time of blood collection in four categories, January-March, April-June, July-September, October-December only and with additional adjustment for first-degree family history of breast cancer (yes/no), number of births (0, 1-2, 3), duration of breast feeding (continuous, in months), age at menarche (<13, [13][14]15), BMI (continuous, in kg/m 2 ) and alcohol consumption (0, 1-18, 18 g ethanol/day). Age at first birth, smoking and education did not affect the estimates considerably and were therefore not included in the final model.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1. We included eleven studies (11)(12)(13)(15)(16)(17)(18)(19)(35)(36)(37) that fully met our inclusion criteria for this meta-analysis. The characteristics of the included studies are summarised in Table 1.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Dietary and lifestyle factors may have an important role in the development of breast cancer (2)(3)(4) , among which Ca intake has been suggested as a potential protective factor in mounting experimental research (5)(6)(7)(8)(9)(10) and several observational studies (11)(12)(13) . A metaanalysis by Chen et al (14) involving six prospective cohorts and nine case-control studies suggested a significant inverse association between Ca intake and risk of breast cancer, with a summary relative risk (RR) of 0·81 (95 % CI 0·72, 0·90) for the highest compared with the lowest intake of Ca, with a significant publication bias.…”
mentioning
confidence: 99%